Transcriptome Sequence Analysis of the Defense Responses of Resistant and Susceptible Cucumber Strains to Podosphaera xanthii - Meng, Xiangnan; Yu, Yongbo; Song, Tiefeng; Yu, Yang; Cui, Na; Ma, Zhangtong; Chen, Lijie; Fan, Haiyan (Frontiers in Plant Science, 2022)
Powdery mildew (PM) caused by Podosphaera xanthii poses a continuous threat to the performance and yield of the cucumber (Cucumis sativus L.). Control in the initial stages of infection is particularly important. Here, we studied the differential physiological and transcriptomic changes between PM-resistant strain B21-a-2-1-2 and PM-susceptible strain B21-a-2-2-2 at the early stage of P. xanthii attack. When challenged with P. xanthii, the tolerant line can postpone the formation of the pathogen primary germ. Comparative transcriptomic analysis suggested that DEGs related to the cell wall and to pathogen and hormone responses were similar enriched in both cucumber lines under P. xanthii infection. Notably, the number of DEGs triggered by P. xanthii in B21-a-2-1-2 was quintuple that in B21-a-2-2-2, revealing that the success of defense of resistant cucumber is due to rapidly mobilizing multiple responses. The unique responses detected were genes related to SA signaling, MAPK signaling, and Dof and WRKY transcription factors. Furthermore, 5 P. xanthii -inducible hub genes were identified, including GLPK, ILK1, EIN2, BCDHβ1, and RGGA, which are considered to be key candidate genes for disease control. This study combined multiple analytical approaches to capture potential molecular players and will provide key resources for developing cucumber cultivars resistant to pathogen stress.